Transcriptomic analysis reveals the mechanism of low/high temperature resistance in an outstanding diet alga Nannochloropsis oceanica - Lin Zhang; Jiaojiao Tian; Lingzhi Ye; Kai Liao; Jichang Han; Song Wang; Jiayi Cao; Zhengwei Ye; Jilin Xu (Aquaculture Reports, 2022)
Low/high temperature stress is one of the key abiotic factors restricting the implementation of microalgal large-scale production. Metabolism, involved in abiotic stress resistances, have been reported in plants, but the related research in microalgae is far behind. This study analyzed the transcriptional changes in Nannochloropsis oceanica under low and high temperature stresses by RNA-seq technology. Results indicated that the total differentially expressed gene (DEG) amount under high temperature stress was much more than low temperature stress. GO enrichment analysis suggested that DEGs under low temperature were mainly concentrated in protein modification and phosphorus metabolic process, while transmembrane transport, lipid localization and transport, and cellular homeostasis were the most enriched terms under high temperature. Moreover, “membrane” was the most enriched term in both low and high temperature groups. The gene expressions of 37 stress resistance-related enzymes/proteins (172 genes) were analyzed concretely in N. oceanica for the first time. Results revealed that ornithine decarboxylase (ODC) was significantly down-regulated, while choline dehydrogenase (CHDH), late embryogenesis abundant (LEA), dehydrin (DHN), chitinase (CHI), calmodulin (CaM), and lipid transfer protein (LTP) were extremely up-regulated under low temperature. Under high temperature, more genes with drastic changes were identified. Superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione synthetase (GSS), and glyoxalase II (Gly II) exhibited down-regulated significantly, while glutathione S-transferase (GST), CHDH, L-asparaginase (L-ASP), LEA, DHN, early response to dehydration protein (ERD), heat shock protein (HSP), and CaM were dramatically up-regulated. No significant changes were detected in glutathione peroxidase (GPX), tocopherol cyclase (TC), gamma-glutamylcysteine synthetase (γ-GCS), pyrroline‐5–carboxylate reductase (P5CR), asparagine synthetase (ASN ), succinate-semialdehyde dehydrogenase (SSADH), pyruvate decarboxylase (PDC), and S-adenosylmethionine synthetase (SAMS) under low or high temperature. Furthermore, 166 transcription factor (TF) genes related to plant stress resistance were characterized and categorized into 20 TF families. MYB was the most abundant and active one, revealing that the MYB family played a critical role of temperature resistance in N. oceanica. These new findings could benefit the understanding of the temperature resistance mechanism in Nannochloropsis. The significantly changed genes might be ideal candidates for breeding elite Nannochloropsis strains with stronger resistance to temperature stress using genetic engineering methods.